2018
DOI: 10.1158/1078-0432.ccr-17-2994
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-Driven Precision Medicine for Advanced Pancreatic Cancer: Early Results from the COMPASS Trial

Abstract: To perform real-time whole genome sequencing (WGS) and RNA sequencing (RNASeq) of advanced pancreatic ductal adenocarcinoma (PDAC) to identify predictive mutational and transcriptional features for better treatment selection. Patients with advanced PDAC were prospectively recruited prior to first-line combination chemotherapy. Fresh tumor tissue was acquired by image-guided percutaneous core biopsy for WGS and RNASeq. Laser capture microdissection was performed for all cases. Primary endpoint was feasibility t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
490
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 484 publications
(513 citation statements)
references
References 48 publications
18
490
0
5
Order By: Relevance
“…It is essential and urgent to crack the secret of the carcinogenesis and progression of PC. Although several transcriptomic (including both mRNA and miRNA) studies conducted previously have provided preliminary assessments of gene expression profiles in PC tissues, systematic analysis using network‐based approaches is quite limited, which would allow us for a better understanding of the pathogenesis of PC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential and urgent to crack the secret of the carcinogenesis and progression of PC. Although several transcriptomic (including both mRNA and miRNA) studies conducted previously have provided preliminary assessments of gene expression profiles in PC tissues, systematic analysis using network‐based approaches is quite limited, which would allow us for a better understanding of the pathogenesis of PC.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of these studies used either cell lines or animal models of PC, or microarray‐based methods that have apparent limitations when compared with RNA‐seq techniques. Very recently, a small number of RNA‐seq‐based transcriptome analyses have been conducted to investigate the gene expression profile changes in pancreatic tissues between different groups of patients (eg, tumor vs non‐tumor, short‐survivor vs long‐survivor) . However, those preliminary studies did not fully demonstrate the complex mRNA‐miRNA interaction network and failed to identify genes and molecular mechanisms that may drive the pathogenesis of PC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This integrative analysis found significant overlap between the different subtypes, ultimately suggesting that PDAC can fundamentally be classified into two major subtypes based on cancer cell autonomous properties: Classical and Basal-like. These subtypes appear to be clinically relevant because the Classical subtype is associated with a better overall survival and better response to first line chemotherapy than the Basal-like subtype (2,4,6).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its overall dismal prognosis, recent research has identified specific molecular subtypes with distinct therapy response and outcome. Among these, the so-called classical phenotype shows improved chemotherapy response and survival compared to the so-called quasimesenchymal or basal-like subtype underlining the urgent requirement for advanced techniques for precise pretherapeutic patient stratification (2,3). This is key to both, adequate patient management, based on informed decision processes, clinical trial design and outcome interpretation.…”
Section: Introductionmentioning
confidence: 99%